النظام القانوني لعقد حفظ الحق في ظل التشريع الجزائري - عارف, نادية (جامعة الوادي University of Eloued, 2018)
"لقد أعاد المشرع الجزائري ضبط عقد حفظ الحق وجعله من عقود الترقية العقارية المنظمة في القانون رقم 11-04 الذي يحدد القواعد التي تنظم نشاط الترقية العقارية بعد أن كان منظما في المرسوم التشريعي رقم 93-03, حيث اعتبر عقد حفظ الحق عقدًا ابتدائيًا لبيع عقار في طور البناء, وبرجوع لنص المادة (27) من القانون رقم 11-04 نجده قد أعطى تعريفا دقيقا للعقد, وبالتالي يتضح لنا من خلاله أن عقد حفظ الحق له خصائص عديدة, أهمها: أنه عقد ملزم لجانبين, بالإضافة إلى وجوب كتابته ووضعه في طابع رسمي, وما يميز هذا العقد عن بقية العقود المشابهة له كعقد البيع على التصاميم والوعد بالبيع. كما أشرنا في دراستنا على الشروط أو الأركان الموضوعية والشكلية لهذا العقد, ومن بين الأركان الموضوعية وجوب التراضي في العقد بالإضافة إلى المحل المتمثل في العقار المراد إنجازه. أما بخصوص الأركان الشكلية لعقد حفظ الحق كان من بينها أنه يجب إفراغ العقد في طابع رسمي, وإلاّ اعتبر هذا العقد باطلا, كذلك يتبين لنا من خلال هذه الدراسة أنه يجب على المرقي العقاري استخراج بعض الوثائق الإدارية, وهذا ما نصت عليه المادة (30) من القانون رقم 11-04 إلى غاية مرحلة تسجيل هذا العقد في المحافظة العقارية, وذلك تطبيقا للمرسوم التنفيذي رقم 13-431. خلاصة القول أن عقد حفظ الحق يلتزم البائع بالإضافة إلى الالتزامات العامة المعروفة, وهي: ( نقل الملكية) هناك الالتزامات جديدة, وهذا نظرا للخصوصية التي يتميز بها هذا النوع من العقود, وهي: الالتزام بتحرير عقد البيع النهائي حيث على المرقي العقاري القيام بتحرير العقد النهائي, وذلك بعد أن يقوم صاحب حفظ الحق بتسديد بقية ثمن العقار, وهذا طبقا لنص المادة (33) من القانون رقم 11-04, بالإضافة إلى الالتزام بمواصلة الإنجاز والمطابقة, وهو ما نصت عليه المادة (17) من القانون رقم 11-04, كذلك على المرقي العقاري الالتزام بتخصيص العقار لصاحب حفظ الحق, بمعنى أنه يمنع على المرقي العقاري القيام بأي تصرف دون ذلك ( بيعه أو استئجاره). أما بالنسبة لالتزامات صاحب حفظ الحق ويتمثل أهم التزام يقع على عاتقه هو دفع تسبيق نقدي طبقا لنص المادة (52) من القانون رق 11-04, كذلك الالتزام الأخير الذي ينقل الملكية العقارية وهو الالتزام بتسديد بقية الثمن, وهو ما نصت عليه المادة (31) من القانون رقم 11-04. وفي حالة إخلال أحد الطرفين بالتزاماته يترتب على ذلك إما فسخ العقد طبقا لنص المادة (32) من القانون رقم 11-04, أو التعويض وهو ما نصت عليه المادة (174) من القانون المدني, بالإضافة إلى جزاءات جزائية الواردة في القانون رقم 11-04, كما سبق كذلك القول أن صندوق الضمان والكفالة المتبادلة له دور أساسي في تطوير نشاط الترقية العقارية باعتباره هيئة ضمان ومراقبة المشاربع, وذلك طبقا لنص المادة (121) من القانون رقم 89-26 المتضمن قانون المالية لسنة 1990. حيث يهدف هذا الصندوق إلى ضمان التسديدات التي يدفعها المشترون, والتي تكمن في تسبيق على طلب إلى المتعاملين في الترقية العقارية, ويجيز هذا الصندوق لأعلى متعامل في الترقية العقارية الانخراط فيه وأن يكتب هذا الأخير تأمينا على المشروع, وذلك بموجب المرسوم التشريعي رقم 93-103 في المادة (11) منه, وهو بعبارة أخرى كفيل عيني للمشتري فيما يخص ديونه على المتعامل في الترقية العقارية, وهذا بموجب المادة (54) من القانون رقم 11-04, حيث يتدخل صندوق الضمان والكفالة المتبادلة في إطار عقد حفظ الحق كهيئة ضان, وذلك طبقا لنص المادة (27/2) من القانون رقم 11-04, ويتم تحديد مبلغ التسبيق بموجب نص المادة (52) من القانون رقم 11-04 بنسبة لا تتجاوز 20% من السعر التقديري للعقار المتفق عليه. " "The Algerian legislator has revoked the contract for the preservation of the right and made it a contract for the promotion of real estate organized in Law No. 11-04, which sets out the rules governing the promotion of real estate after it was regulated by Legislative Decree No. 93-03, The construction phase, and in light of the text of Article (27) of Law No. 11-04 we find it has given a precise definition of the contract, and thus it is clear to us that the contract of preservation of the right has many characteristics, It is binding on two sides, in addition to the need to write and put it in a formal character, and what distinguishes this contract from the rest of the contracts similar to him as the sale contract on the designs and promise to sell. As noted in our study on the conditions or the substantive and formal elements of this contract, and among the substantive elements must be consensual in the contract in addition to the premises of the property to be achieved. As for the formal elements of the contract for the preservation of the right, including that the contract must be emptied in a formal character, otherwise this contract is considered null and void, as evidenced by this study that the real estate developer must extract some administrative documents, Law No. 11-04 until the date of registration of this contract in the real estate province, in application of the Executive Decree No. In summary, the contract of preservation of the right is committed to the seller in addition to the general obligations known, namely: (transfer of ownership) there are new obligations, and this is because of the specificity of this type of contracts, namely: the obligation to edit the final sale contract where the real estate developer to edit the final contract , After the owner of the right to pay the rest of the price of the property, in accordance with the text of Article (33) of Law No. 11-04, in addition to the obligation to continue the completion and conformity, which is provided for in Article (17) of Law No. 11-04, The real estate developer must adhere to the allocation of the property to the right holder, in the sense that it is forbidden to the promoter Akari can do anything without it (sell it or rent it). As for the obligations of the right holder, the most important obligation is to pay cash advances in accordance with Article (52) of Law No. 11-04, as well as the last obligation that transfers real property, the obligation to pay the rest of the price, as stipulated in Article (31) Of Law 11-04. In the event of a breach by one of the parties of its obligations, the contract shall be terminated either in accordance with article 32 of Law No. 11-04 or compensation provided for in Article 174 of the Civil Code, in addition to penal sanctions mentioned in Law No. 11-04 It is also stated that the Mutual Guarantee and Guarantee Fund has a key role in the development of the real estate promotion activity as a guarantee and control body in accordance with the provisions of Article (121) of Law No. 89-26 which includes the Finance Law of 1990. This fund aims at guaranteeing the payments made by the buyers, which lies in applying to the real estate promotion agents. This fund allows the highest real estate promotion agent to enter into it and write the insurance for the project under Legislative Decree No. 93-103. Article (11) thereof, which in other words is a guarantor in the eyes of the buyer in respect of his debts to the agent in the promotion of real estate, and this in accordance with Article (54) of Law No. 11-04, where the mutual guarantee and guarantee fund intervenes under the contract to preserve the right as a body of Article (27/2) of Law No. 11-04, and the amount of the award shall be determined by Article (52) of Law No. 11-04 shall be written at a rate not exceeding 20% ​​of the estimated price of the agreed property."
قانون عقاري
Keywords: عقد حفظ الحق صاحب الحق المرقي العقاري; Hold the right hold His right Mortar Real Estate